Acceleration of the Maillard reaction and achievement of product quality by high pressure pretreatment during black garlic processing. (15th July 2020) - Li, Fangwei; Cao, Jiarui; Liu, Qi; Hu, Xiaosong; Liao, Xiaojun; Zhang, Yan
Highlights: The relationship between high pressure pretreatment and Maillard reaction was analyzed. The reducing sugar balance point was first proposed with a speculated role. The production efficiency was markedly higher with the high pressure pretreatment. Abstract: The efficiency of black garlic processing was improved by acceleration of the Maillard reaction after high-pressure pretreatment. The relationship between component changes and the Maillard reaction was analyzed. Three stages of processing were generalized: 1) at the pretreatment stage, the destruction of the cellular structure by high pressure promoted the enzymatic reaction; 2) from 0 to 3 d, the enzymatic reaction was promoted at 45 °C in damaged cells; and 3) after the 3rd day, heating caused the components to change directly. High-pressure pretreatment damaged the intracellular environment, creating reducing sugars for the Maillard reaction that accumulated during the early processing stage, which directly led to the acceleration of the reducing sugar balance point (RSBP). The application of high-pressure pretreatment shortened the production time of black garlic from 24 d to 15 d. Sensory evaluation was performed, and the quality of the black garlic produced in this innovative way met the commercial requirements.